The Effects of COVID-19/ACE2 on Pregnancy Events and Outcomes: A Systematic Review - Azizeh Sadeghzadeh; Firouzeh Sadeghzadeh; Fariba Mahmoudi (Fasa University of Medical Sciences, 2022)
Background & Objectives: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was confirmed as the cause of Coronavirus disease 2019 (COVID-19). The disease presents with a wide range of clinical signs and symptoms involving vital organs such as the lungs, heart, gastrointestinal tract, liver, central nervous system, blood, and kidneys. It also potentially affects other organs, including the placenta.The present systematic review aimed to evaluate effects of SARS-CoV-2 on pregnant women, fetuses, and infants born to infected mothers. Material & Methods: The search fields used in this study were angiotensin-converting enzyme receptor (ACE2), fetus, pregnancy, and SARS-CoV-2. We reviewed articles published in 2020 and 2022. The inclusion criteria were articles on receptor expression, virus entry into the host cell, studies on the characteristics and outcomes of pregnant or recently pregnant women with SARS-CoV-2 infection who were approved and characteristics and outcomes of infants whose mothers were infected with SARS-CoV-2. Results: The virus uses the ACE2 to enter the cell. The coronavirus can be expected to affect any cell or organ that expresses ACE2. Female reproductive system is one of the systems that express ACE2. The destructive effects of COVID-19 on maternal and fetal health are strongly influenced by the spatial-temporal distribution of ACE2. Conclusion: The harmful role of COVID-19 in pregnancy is highly controversial, although maternal COVID-19 infection contributes to adverse consequences of pregnancy. There is a limited amount of information on the efficacy of COVID-19 on pregnants and their fetuses.